BENEFICIAL EFFECTS OF GRAPE SEED EXTRACT AGAINST CISPLATIN-INDUCED TESTICULER DAMAGE IN RABBITS - Yildirim, Nuran Cikcikoglu; Kandemir, Fatih Mehmet; Benzer, Fulya (Virtual Co Physics Srl, 2011)
Biological compounds with antioxidant properties may contribute to the protection of cells and tissues against deleterious effects of reactive oxygen species (ROS) and other free radicals induced by cisplatin. This study was performed to investigate the possible protective role of antioxidant treatment with grape seed extract (GSE) on cisplatin-induced testes oxidant injury using biochemical approaches. The degree of protection produced by GSE was evaluated by determining the level of malondialdehyde (MDA) and glutathione (GSH), the activity of catalase (CAT), glutathione peroxidase (GSH-Px), were estimated from testes of rabbits. Male New Zealand white rabbits were divided into 3 groups (n=6): 1-Control group(1 ml saline. i.p) 2-Cisplatin group (a single dose of cisplatin (5 mg/kg, i.p) 3-A single dose of cisplatin (5 mg/kg, i.p) + GSE (250 mg/kg/day, i.p) for 6 days. MDA level were significantly higher when compared to Control (p < 0.05). In Cisplatin+grapes groups MDA levels were found significantly lower than cisplatin group (p < 0.05). GSH levels were decreased with cisplatin compared to control but in case of cisplatin+ GSE it increased (p < 0.05). In treated rabbits, the activity of CAT and GSH-Px was decreased in cisplatin and cisplatin+ GSE groups compared to control (p < 0.001). These results indicate that the antioxidant GSE might have a protective effect against cisplatin-induced testiculer damage and oxidative stress in rabbit.
Keywords: Grape seed extract; Cisplatin; Testicular damage; Rabbit